THE PRESSURES AND TEMPERATURES OF FORMATION OF DIAMOND BASED ON THERMOBAROMETRY OF CHROMIAN DIOPSIDE INCLUSIONS - Nimis P. (My University, 2002)
To date, the evaluation of the temperature (T) and pressure (P) of formation of natural diamond has generally relied on thermobarometry of rare polymineralic inclusions containing appropriate assemblages of minerals. The results are commonly ambiguous, because of potential re-equilibration of touching minerals after diamond growth and possible disequilibrium between non-touching minerals. Here, I calculate T and P for over one-hundred inclusions of chromian diopside (mostly isolated) in diamond crystals containing inclusions of peridotitic material, and for peridotite xenoliths from worldwide occurrences, using single-clinopyroxene thermobarometers. The results provide constraints on the conditions and relative timing of diamond genesis. Inclusions in diamond and xenoliths from the same source commonly yield similar P–T values, suggesting that diamond crystals formed when the lithospheric mantle had already attained a conductive thermal regime comparable to or even colder than that extant at the time of emplacement of the host kimberlite or lamproite. Some inclusions record thermal or metasomatic events, which can be ascribed to the ascent of hot C-rich fluids from which the diamond precipitated. In a few cases, secular cooling of the cratonic lithosphere is believed to be a possible source of scatter in T estimates. In general, there is no evidence for occurrences of diamond being concentrated at particular levels in the lithosphere. Where significant gaps occur in the distribution of diamond crystals with included lherzolitic material, they are associated with a scarcity of lherzolitic material in the mantle and do not necessarily correspond to a real absence of diamond crystals. The results support the use of chromian diopside thermobarometry as a complementary tool for assessment of diamond potential in exploration programs.